Synectic Model: Unleashing Creative Expression in Students' Narrative Writing Skills - Henanggil, Mita Domi Fella; Abdurahman, Abdurahman; Asmawati, Asmawati (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aimed to investigate the effectiveness of the synectic model in enhancing students' narrative writing skills. A quasi-experimental design was employed, involving 60 participants randomly assigned to either a control group or an experimental group. Data collection utilized pretests and posttests to assess students' writing performance. Analysis involved calculating mean scores and employing t-tests and gain score analysis to determine the impact of the synectic model. The results revealed a significant increase in narrative writing abilities among students in the synectic model group compared to the control group. This suggests that the synectic model effectively promotes creative thinking and diverse perspectives, making it a valuable tool for educators to improve students' narrative writing skills. The study highlights the potential of the synectic model in fostering narrative writing skills. Educators can integrate this model into their curriculum to enhance students' writing abilities. Further research is recommended to explore the model's effectiveness in different contexts and grade levels.